FICTIONAL RECONSTRUCTION AND SOCIAL RECONSTRUCTION OF REALITY - Ștefan VLĂDUȚESCU (Annals of the University of Craiova for Journalism, Communication and Management)
The present study investigates a particular case of the theory of social reconstruction of reality, namely the case of literary reconstruction. It investigates how to reconstruct fictionally the most fruitful existential and philosophical period in the life of Friedrich Nietzsche. The Corpus analyzed is Irvin D. Yalom's documentary novel, "Nietzsche's Weeping." It is found that for the reconstruction of reality, four operations are applied (lie, seduction, fiction and myth). It is concluded that the theory of YALOM, 2006, P. L. Berger and T. Luckmann regarding the social reconstruction of reality is also verified in the case of literary communication.